Problem solving strategies of Malaysian secondary school teachers - Dorothy, D.; Alias, N.; Siraj, Saedah (2016)
Higher order thinking skills are needed for problem-solving which is the highest level of cognitive knowledge. However, studies seem to indicate that Malaysian students lack problem solving and higher order thinking skills. Teachers do not seem to inculcate higher order thinking skills for problem solving. The purpose of this study is to investigate the problem solving strategies teachers use during instruction. A total of 131 science secondary school teachers in a selected state in Malaysia were surveyed to determine the strategies used. The results indicate that teachers prefer teaching facts, and asking students to listen to the teachers’ explanation. The dominant problem solving strategy teachers use is making analogies to similar problems. Further research is required to develop instructional models with strategies for problem solving in the Malaysian context. This will enable teachers to use the model to develop higher order thinking among students.